Effect of Fermented Corn-Soybean Meal on Serum Immunity, the Expression of Genes Related to Gut Immunity, Gut Microbiota, and Bacterial Metabolites in Grower-Finisher Pigs - Lu, Junfeng; Zhang, Xiaoyu; Liu, Yihao; Cao, Haigang; Han, Qichun; Xie, Baocai; Fan, Lujie; Li, Xiao; Hu, Jianhong; Yang, Gongshe; Shi, Xin’e (Frontiers in Microbiology, 2019)
Fermented corn-soybean meal (fermented feed, FF) is commonly used in swine production, but the effects of FF on gut health remain unclear. In this study, serum immunity, mRNA abundances of antimicrobial peptides (AMPs) and Toll-like receptors (TLR1-9), bacterial abundance in the duodenum and colon, and colonic metabolic phenotypes were determined in crossbred barrows (Duroc × Landrace × Large White) fed FF or normal feed(unfermented feed, UF) (n = 6). When compared to the UF group, the results showed that serum levels of IgG and IgM were significantly increased in FF group pigs (P < 0.05). FF significantly decreased the abundances of Bacteroides and Verrucomicrobia in the duodenum and decreased the abundances of Bacteroides, Proteobacteria and Verrucomicrobiain in the colon while significantly increased the abundances of Firmicutes and Actinobacteria (P < 0.05). Furthermore, a spearman's correlation analysis showed that serum immunity and expression of genes related to gut immunity were associated with bacterial strains at the family level. Moreover, differentially abundant colonic microbiota was associated with colonic metabolites. LC-MS data analyses identified a total of 1,351 metabolites that had markedly differed between the UF and FF groups. C5-Branched dibasic acid metabolism was significantly upregulated whereas the purine metabolism was significantly downregulated (P < 0.05) in the colonic digesta of pigs in the FF meal group compared to the UF meal group. Collectively, these results indicate that FF meal could influence serum immunity and expression of genes related to gut immunity correlating with the gut microbiota and bacterial metabolites in grower-finisher pigs. This study may provide an alternative strategy for improving the intestinal health of grower-finisher pigs.